(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The purpose of this study is to explore methods of using the famous song “Where the Wind Blows” (Barami Bureooneun Got) by singer Kim Kwang-seok as a teaching material for instructing Korean to foreign learners. This song contains lyrical expressions in Korean and reflects the cultural sentiments characteristic of Korean youth in the 1990s, such as romantic longing for freedom and escape from reality. Based on theories of linguistic and cultural education, the study analyzes the educational value of metaphorical expressions and key grammatical elements included in the lyrics. On this basis, a three-stage teaching–learning model is proposed along with specific classroom activities designed to develop emotional empathy and students’ ability to use metaphorical expressions at intermediate and advanced levels. Ultimately, this study aims to demonstrate that Korean language education can become a humanistic approach that goes beyond simple language acquisition, fostering an understanding of deep Korean emotions and values, and contributing to the creation of an empirical foundation for subsequent research.